2019
DOI: 10.1002/ange.201910625
|View full text |Cite
|
Sign up to set email alerts
|

Imparting Multifunctionality by Utilizing Biporosity in a Zirconium‐Based Metal–Organic Framework

Abstract: In this work, we have synthesized nanocomposites made up of a metal–organic framework (MOF) and conducting polymers by polymerization of specialty monomers such as pyrrole (Py) and 3,4‐ethylenedioxythiophene (EDOT) in the voids of a stable and biporous Zr‐based MOF (UiO‐66). FTIR and Raman data confirmed the presence of polypyrrole (PPy) and poly3,4‐ethylenedioxythiophene (PEDOT) in UiO‐66‐PPy and UiO‐66‐PEDOT nanocomposites, respectively, and PXRD data revealed successful retention of the structure of the MOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The simulation was carried out at constant temperature and constant volume using the Nosé–Hoover thermostat (NVT) with a characteristic time of 50 fs. In the temperature range T = 27–90 °C, host 1 has small vibrational motions, but its center of mass does not move, which suggests that the host is stable enough to keep intact its columnar structure, consistent with the experimental observations of single-crystal-to-single-crystal guest exchange. , …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The simulation was carried out at constant temperature and constant volume using the Nosé–Hoover thermostat (NVT) with a characteristic time of 50 fs. In the temperature range T = 27–90 °C, host 1 has small vibrational motions, but its center of mass does not move, which suggests that the host is stable enough to keep intact its columnar structure, consistent with the experimental observations of single-crystal-to-single-crystal guest exchange. , …”
Section: Resultssupporting
confidence: 81%
“…The columns run parallel to the crystallographic b axis and adopt a pseudohexagonal rod-packing arrangement (see Figure S14). Next, host 1 (5–10 mg) was exposed to guest vapor by heating the guests to their sublimation temperature (40 °C for Py and 90 °C for EDOT) under vacuum for ∼24 h. , The resulting host–guest complexes remained colorless, and their structures were evaluated by single-crystal X-ray diffraction (SC-XRD).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, recent studies have revealed that polymeric guests formed inside porous MOFs via the in situ polymerization of preloaded monomers can not only improve the structural stability and porosity of certain collapse-prone frameworks but also introduce a large number of functional groups that can create new properties and functions in the resulting MOF/polymer composites. For example, in situ generated conducting polymers (CPs) have transformed insulating MOFs into semiconducting MOF/CP composites, MOF/polymer composites have been used to extract heavy-metal ions, such as Hg, Au, Pb, and Pd ions, from aqueous solutions, , and a MOF/polydopamine (PDA)/Pd nanoparticle composite was able to catalyze the Suzuki coupling reaction . However, the electrical conductivity of MOF/polymer/metal nanoparticle (MNP) composites has been largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconducting metal–organic frameworks (MOFs) with permanent porosity, ultralow density, and tunable electrical conductivity are in high demand due to their diverse potentials to serve as active components of myriad electronics and clean energy production, transport, and storage devices, such as rechargeable batteries, supercapacitors, transistors, , chemiresistive sensors, and electrocatalysts. Despite remarkable recent advances, generating high intrinsic electrical conductivity in 3D porous MOFs and covalent–organic frameworks (COFs) remains a challenging task chiefly because they often lack efficient well-defined through-bond and/or through-space charge transport pathways. ,, One way to boost the electrical conductivity of highly porous MOFs is to introduce appropriate guest molecules, such as node-coordinating conjugated π-systems, which can bridge coordinatively unsaturated nodes, thereby promoting through-bond charge transport or redox-complementary π-intercalators that can form extended π-donor/acceptor stacks with the preorganized ligands and thus facilitate through-space charge transport. Another strategy to facilitate charge transport across porous MOFs entails in situ polymerization of preloaded monomers into conducting polymers (CPs), such as polyaniline, polypyrrole, polythiophene, and polyethylenedioxythiophene (PEDOT), inside MOF pores, …”
Section: Introductionmentioning
confidence: 99%